2015
DOI: 10.1007/s10450-015-9746-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of geometric heterogeneity of closed carbon nanotube bundles on benzene adsorption from the gaseous phase-Monte Carlo simulations

Abstract: Benzene adsorption from the gaseous phase at 298 K and the thermodynamics of this process using Monte Carlo methods is studied. A series of closed single-walled carbon nanotube (SWCNT) bundles (triangular packing arrangement) with various distance between nanotubes is investigated. Isolated closed nanotube is treated as the reference system. Benzene is considered as a model compound to represent aromatics. Simulation results show the significant effect of the geometric heterogeneity on benzene adsorption as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…(12) in Barrer and Gibbons 1963b;Clark 1970, p. 39;Eq. (2.70) in Rouquerol et al 1999) where s G P � = s G � is for the standard state at temperature T; consequently, according to Gauden et al 2016;Kowalczyk et al 2017), we get:…”
Section: The Accepted Theoretical Dependenciesmentioning
confidence: 83%
See 2 more Smart Citations
“…(12) in Barrer and Gibbons 1963b;Clark 1970, p. 39;Eq. (2.70) in Rouquerol et al 1999) where s G P � = s G � is for the standard state at temperature T; consequently, according to Gauden et al 2016;Kowalczyk et al 2017), we get:…”
Section: The Accepted Theoretical Dependenciesmentioning
confidence: 83%
“…(3) and (4), ∆H is the isosteric enthalpy of adsorption (∆H < 0 and q st = −ΔH), which is practically the same as the differential molar enthalpy [q diff = q st − RT Gauden et al 2016;Kowalczyk et al 2017), and this is…”
Section: The Accepted Theoretical Dependenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…CNTs are an important carbon‐based adsorptive material with exceptional adsorption capabilities and high adsorption efficiency for various organic pollutants . CNTs are particularly promising as a benzene adsorbent for environmental protection/remediation . For example, in the study of Abbas et al CNTs impregnated with iron oxide nanoparticles were employed for the removal of benzene from water.…”
Section: Introductionmentioning
confidence: 99%
“…Elsehly et al investigated the performance of CNT‐based filter for benzene removal from aqueous solutions, and they indicated that the filters were efficient for benzene removal. Gauden et al studied the benzene adsorption on CNT bundles from gaseous phase using Monte Carlo methods, and showed the significant effect of the geometric heterogeneity on benzene adsorption.…”
Section: Introductionmentioning
confidence: 99%